Factores de riesgo para infecciones respiratorias altas recurrentes en preescolares del Barrio Colinas Lojanas de la provincia de Loja, periodo diciembre 2015-mayo 2016. - Japón Gualán, Hugo Germán (2017)
High respiratory infections (go high) are a complex sindromatico of clinical entities, with epidemiological and causal diversity that makes it difficult to control and surveillance, becoming the most frequent pediatric consultation. (Ciria et al., 2012) The objective of this research was to determine and analyze the risk factors and its relationship with high respiratory infections in preschool children of the Lojanas hills neighborhood. We used a sample of 60 children who met the inclusion criteria, the information was processed through the application of a survey representative of the child, obtained the following results: Male found 72% (n = 23) of common cold and 28% (n = 9) of sore throat. Female gender was evident common cold in a 71% (n = 28) and 29% (n = 9) of sore throat. With regard to risk factors triggering the development of infections respiratory high was found mainly dust with 85% (n = 51), climatic changes with 73% (n = 44), and the presence of tobacco smoke in the home with 67% (n = 40), coming to the conclusion that the most frequent pathology is the common cold whose main risk factor is dust. Key words: Infections respiratory high; Preschool; Risk factors.